1993
DOI: 10.1016/0042-6989(93)90230-t
|View full text |Cite
|
Sign up to set email alerts
|

The spectral properties of the two rod pathways

Abstract: Psychophysical and electroretinographic observations in normal and achromat observers suggest that rod flicker signals have access to at least two retinal pathways: one (q,), slow and sensitive, predominating at scotopic luminance levels, the other (a;), fast and insensitive, predominating at mesopic ones. We have measured steady-state flicker detection sensitivities on background fields ranging from 430 to 640 nm in normal observers. Our results suggest that cone signals can reduce the sensitivity of s;, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…However, for a flicker of 15 Hz, the perception of flicker diminishes for flash strengths above the flicker threshold. At higher flash strengths, the perception of flicker reappears and becomes more pronounced [8][9][10][11][12]. In later studies, this disappearance of flicker perception was found to correlate with a minimum in the amplitude versus flash strength curve of 15 Hz flicker electroretinograms (ERGs) [13,14].…”
Section: Introductionmentioning
confidence: 92%
“…However, for a flicker of 15 Hz, the perception of flicker diminishes for flash strengths above the flicker threshold. At higher flash strengths, the perception of flicker reappears and becomes more pronounced [8][9][10][11][12]. In later studies, this disappearance of flicker perception was found to correlate with a minimum in the amplitude versus flash strength curve of 15 Hz flicker electroretinograms (ERGs) [13,14].…”
Section: Introductionmentioning
confidence: 92%
“…Inset shows the experimental conditions: a 6 deg diameter, 500 nm target was presented in the centre of an 11.5 deg diameter, 668 nm background at an eccentricity of 13 deg. Based on data from Sharpe et al. (1993b).…”
Section: Complexities Of Mesopic Photometrymentioning
confidence: 99%
“…5,[27][28][29][30][31][32][33] However, psychophysical investigations suggest that there is little or no difference between the spatial extents of the neural excitation pools of the two signals. 28,31 Moreover, if the differences between rod and cone motion is largely due to filtering by the rod photoreceptors themselves or to the early spatial and temporal summing of their signals (or both), rather than to the subsequent retinal pathway characteristics, then no change of perceived velocity with a change in luminance should be expected.…”
Section: Two Retinal Pathwaysmentioning
confidence: 99%
“…[22][23][24][25][26] Psychophysical and electrophysiological studies in man support an analogous rod duality in the human visual system; the clearest signature of which is a loss of flicker visibility and a corresponding reduction in electroretinographic response amplitude at frequencies near 15 Hz and at intensities near 0 log scotopic td caused by destructive interference between slow (low intensity) and fast (high intensity) rod signals. 5,[27][28][29][30][31][32][33] Are these slow and fast rod flicker signals correlated with the two cortical motion systems? Does the rod visual system at low intensities, at which only the slow retinal pathway is functioning, have access to the fast cortical motion system?…”
mentioning
confidence: 99%